Impact of cost overrun factors on the project delay in construction industry, Pahang, Malaysia - Zhi Jia, Ling (2014)
This thesis is about impact of cost overrun to the project delay in the project life cycle. This study will focus on the Grade 7 construction companies in the Pahang. 40 project managers and site contractors from the construction industry in Pahang participated in the survey questionnaire. There are two variable in this study which are independent variables (Cost overrun factors) and dependent variable (Project delay). Reliability test is used to identify whether the variable is reliable or not. The result of Cronbach’s Alpha for all variables shows that the involved variables are reliable ranging from 0.874 to 0.951. Single mean t-test is used to identify the environmental factor which shows a high value of 4.37. Pearson correlation results indicate that the all the cost overrun factors has a positive relationships with the project delay. Finding in this study is beneficial to employer to understand how important cost overruns factors to project delay, as well as to prevent recurrences from happening in construction industry